2023
DOI: 10.1051/0004-6361/202245716
|View full text |Cite
|
Sign up to set email alerts
|

Multiple injections of energetic electrons associated with the flare and CME event on 9 October 2021

Abstract: Context. We study the solar energetic particle (SEP) event observed on 9 October 2021 by multiple spacecraft, including Solar Orbiter. The event was associated with an M1.6 flare, a coronal mass ejection, and a shock wave. During the event, high-energy protons and electrons were recorded by multiple instruments located within a narrow longitudinal cone. Aims. An interesting aspect of the event was the multi-stage particle energisation during the flare impulsive phase and also what appears to be a separate phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…within the 1-20 keV suggest the presence of a hotter thermal component. Interestingly, in a rare published example of electron peak intensity energy spectra, i.e., Jebaraj et al (2023) produced by the SolO Energetic Particle Detector (STEP, EPT, and HET; Rodríguez-Pacheco et al 2020), we see a flattening (Kontar & Reid 2009) but then a noticeable upturn in the energy spectrum at lower energies (at around 10-20 keV), which may indicate the signature of the accelerating plasma environment. Nevertheless, this provides an excellent example of why this spectral region deserves more attention and analysis.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…within the 1-20 keV suggest the presence of a hotter thermal component. Interestingly, in a rare published example of electron peak intensity energy spectra, i.e., Jebaraj et al (2023) produced by the SolO Energetic Particle Detector (STEP, EPT, and HET; Rodríguez-Pacheco et al 2020), we see a flattening (Kontar & Reid 2009) but then a noticeable upturn in the energy spectrum at lower energies (at around 10-20 keV), which may indicate the signature of the accelerating plasma environment. Nevertheless, this provides an excellent example of why this spectral region deserves more attention and analysis.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…A more recent study by Dresing et al (2023) used multi-spacecraft radio observations to infer the presence of a series of distinct SEP injections with significantly different propagation directions, which formed a complex widespread multi-spacecraft SEP event. Another recent study by Jebaraj et al (2023) showed both a flare and shock contribution to the acceleration of relativistic electrons, with the shock contribution supported by the presence of herringbone bursts. Up until recently, due to the limited radio imaging observations available during SEP events, especially imaging of herringbones, along with the scarcity of spacecraft monitoring the Sun within 1 AU, a spatial connection to the trajectory of radio emission and the injection sites of electrons inferred from spacecraft locations could not be investigated in detail.…”
Section: Introductionmentioning
confidence: 93%
“…While solar flares were originally considered to be the main source of solar energetic electrons (Lin et al 1982;Reames 1999), type II radio bursts provide proof of shockaccelerated electrons in the energy range of a few to tens of keV (Mann & Klassen 2005). However, the acceleration of electrons up to MeV energies remains elusive and strongly debated (e.g., Kahler et al 2007;Klein & Dalla 2017;Dresing et al 2020;Jebaraj et al 2023). A surprising result of a statistical analysis comparing peak intensities of solar energetic electron events with coronal shock parameters at the location of the magnetic footpoint of the observing spacecraft (Dresing et al 2022) was that MeV electrons showed higher correlations with shock parameters than <100 keV electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2023) investigated the evolution of the CME associated with the SEP event and its interaction with the structured solar wind. Jebaraj et al (2023) examined the acceleration of electrons by both the solar flare temporally associated with the parent solar eruption and by the shock driven by the corresponding CME. Finally, Wijsen et al (2023) simulated the propagation of the CME-driven shock and the ESP event at two of the five observers using the European Heliospheric FORecasting Information Asset (EUHFORIA; Pomoell & Poedts, 2018) and PArticle Radiation Asset Directed at Interplanetary Space Exploration (PARADISE; Wijsen et al, 2019) models.…”
Section: Introductionmentioning
confidence: 99%
“…For the solar flare source, we use as the SEP injection time the peak time of the associated GOES X-ray emission, i.e., 06:38 UT (we note that Jebaraj et al, 2023, reported a radio Type III emission starting at 06:31 UT, which could be used as an alternative constraint), and employ an exponential decay time that is scaled with the flare class, under the assumption that this parameter is related to the duration of the X-ray emissione.g., Kahler & Ling (2022) showed that stronger flares tend to decay over longer time scales, possibly due to the longer duration of the related reconnection processes. For the coronal shock source, we use the onset time of the corresponding radio Type II emission (considered a signature of a formed CME-driven shock; e.g., Vršnak & Cliver, 2008;Magdalenić et al, 2010), i.e., 06:33 UT according to the analysis performed by Jebaraj et al (2023) employing ground-based observations. In this case, we also use an exponential decay time profile, but with a time constant calculated from the transit time of the CME through the corona to the Enlil inner boundarywe remark that this choice has no physical basis, but allows for a smooth transition from the coronal shock source to the default interplanetary one.…”
Section: Introducing the Fixed-source Option In Sepmodmentioning
confidence: 99%